Psychological Distress Symptoms Associated With Life Events in Patients With Bipolar Disorder: A Cross-Sectional Study - Sato, Aiko; Hashimoto, Tasuku; Kimura, Atsushi; Niitsu, Tomihisa; Iyo, Masaomi (Frontiers in Psychiatry, 2018)
Stressful life events, although less serious than traumatic experiences, affect the clinical course of patients with bipolar disorder. We previously found that bipolarity in patients with major depression is related to the severity of psychological distress symptoms associated with onset-related events. Here, we investigated whether, and to what extent, bipolar patients perceive stressful events as psychological distress symptoms, specifically, intrusion, avoidance, and hyperarousal. Further, we investigated the relationship between the clinical features and the severity of psychological distress symptoms associated with stressful life events, according to mood states. We recruited 79 bipolar patients (depression group, n = 32; mania, n = 22; euthymia, n = 25) in this cross-sectional study. We adopted the Impact of Event Scale-Revised (IES-R) to assess the severity of psychological distress symptoms associated with past stressful events. We also evaluated the Hamilton Depression Rating Scale (HDRS) and the Young Mania Rating Scale (YMRS). The mean (standard deviation) IES-R scores of bipolar patients with a depressive episode (38.06 [16.56], p = 0.0005) and of those with a manic/hypomanic episode (44.56 [24.14], p = 0.004) were significantly higher than of those with euthymia (19.81 [12.86]). The HDRS, but not the YMRS, scores showed significant correlations with the IES-R scores, regardless of mood episodes (depression group, r = 0.42; mania, r = 0.64; euthymia, r = 0.70). This study demonstrates that bipolar patients with a manic/hypomanic or depressive episode perceive stressful life events as more severe psychological distress symptoms than do euthymic patients. Moreover, in patients with bipolar disorder, the severity of depressive symptoms, but not of manic symptoms, is positively correlated with that of the psychological distress symptoms, regardless of their mood episodes or euthymic state. Therefore, depressive symptoms may be closely related to the psychological distress symptoms associated with stressful past events in patients with bipolar disorder.